Women in development 02 - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
Women in development in Southern Africa; an annotated bibliography Volume I Botswana compiled by L Ramore 82pp ISBN 92 9081082 3, Volume II Lesotho compiled by M M Chadzingwa 46pp ISBN 92 9081083 1, Volume III Malawi compiled by G W P Kishindo 114pp